Antioxidant Activity, Enzyme Inhibition Potentials, and Phytochemical Profiling of Premna serratifolia L. Leaf Extracts - Adelina Simamora; Adit W. Santoso; Kris H. Timotius; Ika Rahayu (International Journal of Food Science)
Premna serratifolia, commonly known as Arogo in Tentena-Sulawesi, is a popular vegetable. As a promising herbal tea and food ingredient, further investigation is required to find the best knowledge for medicinal use of P. serratifolia leaves. This research investigated the antioxidant activity of the ethanol (EEPS) and water (WEPS) extracts of P. serratifolia leaves, based on their scavenging activities on DPPH radicals and their reducing capacities (CuPRAC, total antioxidant/phosphomolybdenum, and ferric thiocyanate reducing power assays). The DNA-protecting effect by EEPS was tested using pBR322 plasmid DNA against •OH radical-induced damage. The inhibition potentials of both extracts against several enzymes related to metabolic diseases (α-glucosidase, α-amylase, xanthine oxidase, and protease) were evaluated. The phytochemical analysis was conducted by an LC-QTOF-MS/MS technique. EEPS proved to be a better antioxidant and had higher phenolic content compared to WEPS. EEPS demonstrated a protective effect on DNA with recovery percentage linearly correlated with EEPS concentrations. Strong inhibition on α-glucosidase and α-amylase was observed for EEPS; however, EEPS and WEPS showed weak inhibitions on xanthine oxidase and protease. LC-QTOF-MS/MS analysis identified seven main components in EEPS, namely scroside E, forsythoside A and forsythoside B, lavandulifolioside, diosmin, nobilin D, campneoside I, and isoacteoside. These components may be responsible for the observed enzymes inhibitions and antioxidant properties. Premna serratifolia leaves can be an appropriate choice for the development of nutraceutical and drug preparations.